Asymptomatic Carotid Stenosis Is Associated With Circadian and Other Variability in Embolus Detection - Abbott, Anne L.; Merican, Julia; Pearce, Dora C.; Juric, Ana; Worsnop, Christopher; Foster, Emma; Chambers, Brian (Frontiers in Neurology, 2019)
Background and purpose: Variability in transcranial Doppler (TCD) detection of embolic signals (ES) is important for risk stratification. We tested the effect of time of day on ES associated with 60-99% asymptomatic carotid stenosis. Materials and methods: Subjects were from the Asymptomatic Carotid Stenosis Embolus Detection (ASED) Study such that half were previously ES-positive and half ES-negative with 6-monthly 60-minute TCD monitoring. All underwent bilateral TCD monitoring for two 12-hour sessions separated by 24 hours. ES detection rates were calculated using 6-hour and 4-hour intervals from midnight and effective TCD monitoring time. Results: 10 subjects (8 male, mean age 79.5 years) were monitored. Over 24 hours, 5/10 study arteries with 60-99% asymptomatic carotid stenosis were ES-positive (range 1-28 ES/artery, 56 total ES from 177.9 total effective monitoring hours). The remaining 5 study arteries and all 8 successfully monitored contralateral arteries were ES-negative. Using 6-hour intervals the mean ES detection rate peaked at 0600-midday (0.64/hour) and was lowest 1800-midnight (0.09/hour) with an incidence rate ratio of 7.26 (95% CI 2.52 - 28.64, P=<0.001). Using 4-hour intervals the mean ES detection rate peaked at 0800-midday (0.64/hour) and was lowest midnight-0400 (0.12/hour) with an incidence rate ratio of 5.51 (95% CI 1.78 - 22.67, P=0.001). Conclusions: Embolism associated with asymptomatic carotid stenosis shows circadian variation with highest rates four-six hours before midday. This corresponds with peak circadian incidence of stroke and other vascular complications. These and ASED Study results show that monitoring frequency, duration and time of day are important in ES detection.